Kekuatan Makna Ungkapan Bijak Dalam Novel “Rindu” dan “Pukat” Karya Tere Liye: Kajian Semantik - Rahmawati H (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
Language has an important position in human life, namely as a communication tool that connects individuals with each other. The irreplaceable role of language forces humans to be able to master language. Effective communication can be achieved if there is the same meaning between the communicator and the communicant regarding the message conveyed. The research aims to explain the form of wise expressions in the novels "Rindu" and "Pukat" by Tere Liye; the meaning of wise expressions contained in each wise expression in conversation; and the power of the meaning of wise expressions in conversation to make the writer a character. The research design used was descriptive qualitative with semantic studies and the sample in this study was 44 respondents. The results show that there are four forms of wise expressions used in Tere Liye's two works, namely wise expressions of advice, ethics/morals, education, and religion. The meanings contained in wise expressions in conversations according to Djajasudarma's theory in the novel "Rindu" include broad, emotive, dramatic, propositional, central, fictional and idiomatic meanings. Meanwhile, the meaning of wise expressions in "Pukat" includes broad meaning, motif, dramatic, propositional, central, pictorial and idiomatic.